2013
DOI: 10.1002/j.1532-2149.2013.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed radiofrequency inhibited activation of spinal mitogen‐activated protein kinases and ameliorated early neuropathic pain in rats

Abstract: Background: Pulsed radiofrequency (PRF) has been widely used to treat chronic pain, but the effectiveness and mechanisms in preventing early neuropathic pain have not been well explored. Even fewer knowledge is available in its impact on glia-mediated nociceptive sensitization. This study aims to elucidate the modulation of PRF on nerve injury-induced pain development and activation of spinal mitogen-activated protein kinases (MAPKs). Methods: In a rat spinal nerve ligation (SNL) model, a low-volt PRF treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 57 publications
2
47
1
Order By: Relevance
“…Similarly, Lin et al . demonstrated that PRF inhibited ERK activation, which was detected on the third day after surgery [39]. Taken together, our results strongly suggest that immediate PRF treatment regulates ERK-mediated mechanisms in the spinal dorsal horn of SNI rats, which in turn reduces SNI-induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similarly, Lin et al . demonstrated that PRF inhibited ERK activation, which was detected on the third day after surgery [39]. Taken together, our results strongly suggest that immediate PRF treatment regulates ERK-mediated mechanisms in the spinal dorsal horn of SNI rats, which in turn reduces SNI-induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 66%
“…Lin et al . found that early PRF treatment suppressed the levels of proinflammatory cytokines via neuromodulation and immune modulation, such as the downregulation of spinal MAPK (ERK) activation [39]. Therefore, we assumed that an immediate or early PRF intervention may result in less neuroinflammation compared with a delayed PRF intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andre'E aptly pointed out, using different stimulation parameters on different nerve were an important issue for clinical to treat detrusor overactivity [7]. Our research team recently used pulsed radio-frequency (PRF) electrical stimulation to successfully inhibit C-fiber excitatory responses and obstruct the pain conduction signal, the effect can maintain for 3-6 months [8,9]. To the best of our knowledge, few studies explored the feasibility of PRF electrical stimulation in the treatment of detrusor overactivity.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that pulsed radiofrequency (PRF) electrical stimulation can successfully inhibit C‐fiber afferent responses and block pain conduction signals for 3‐6 months …”
Section: Introductionmentioning
confidence: 99%